Pengaruh Model Problem Based Instruction Melalui E-Learning Terhadap Kemampuan Berpikir Kritis Peserta Didik Materi Perpindahan Kalor Kelas V SDN Jatisampurna X - Iis Giri Budiarti (Jurnal Inovasi Pendidikan Dasar, 2021)
School as an education provider institution is responsible for helping students develop critical thinking skills. The learning process in schools is still dominated by teachers in presenting information in one direction, this happens because the sources of information or material sources for students are only teachers and existing thematic books. This makes students passive, learning is less attractive so that the teaching and learning process does not encourage the achievement of students to think critically and students become saturated. This study aims to determine whether there is an effect of critical thinking skills using the Problem Based Instruction model on grade V students at SDN Jatisampurna X in Semester 2 of the 2019/2020 academic year. The research method used was an experimental design with a Pre-Experimental design in the form of One Group Pretest Posttest, the sample used was saturated samples. The population in this study were all students in class V, amounting to 57 students and the sample used was class V-A totaling 27 students. The data collection technique was done through a written test (pretest-posttest). The data analysis technique used the lilliefors normality test, Fisher's test, and the t-test for two different means of paired data. The results showed that the application of the problem-based instruction model affected the critical thinking skills of students in the heat transfer material around us. Keywords: Problem Based Instruction Model, Critical Thinking Ability.